Describing the density of high-level trauma centers in the 15 largest US cities - Karl Y Bilimoria; Deborah M Stein; Marie L Crandall; Anne M Stey; Alexandria Byskosh; Caryn Etkin; Robert Mackersie (Trauma Surgery & Acute Care Open)
Background There has been a proliferation of urban high-level trauma centers. The aim of this study was to describe the density of high-level adult trauma centers in the 15 largest cities in the USA and determine whether density was correlated with urban social determinants of health and violence rates.Methods The largest 15 US cities by population were identified. The American College of Surgeons’ (ACS) and states’ department of health websites were cross-referenced for designated high-level (levels 1 and 2) trauma centers in each city. Trauma centers and associated 20 min drive radius were mapped. High-level trauma centers per square mile and per population were calculated. The distance between high-level trauma centers was calculated. Publicly reported social determinants of health and violence data were tested for correlation with trauma center density.Results Among the 15 largest cities, 14 cities had multiple high-level adult trauma centers. There was a median of one high-level trauma center per every 150 square kilometers with a range of one center per every 39 square kilometers in Philadelphia to one center per596 square kilometers in San Antonio. There was a median of one high-level trauma center per 285 034 people with a range of one center per 175 058 people in Columbus to one center per 870 044 people in San Francisco. The median minimum distance between high-level trauma centers in the 14 cities with multiple centers was 8 kilometers and ranged from 1 kilometer in Houston to 43 kilometers in San Antonio. Social determinants of health, specifically poverty rate and unemployment rate, were highly correlated with violence rates. However, there was no correlation between trauma center density and social determinants of health or violence rates.Discussion High-level trauma centers density is not correlated with social determinants of health or violence rates.Level of evidence VI.Study type Economic/decision.